Biggest concerns of school personnel about students raised by grandparents. (July 2019) - Peterson, Tina L.; Scott, Cathy B.; Ombayo, Bernadette; Davis, Tonya; Sullivan, Dana
Abstract: An electronic survey was administered to school personnel in the state of Kentucky to examine their biggest concerns about students raised by grandparents. Targeted school personnel were teachers, administrators, youth family service staff, and guidance counselors. 188 school personnel answered the question "What is the biggest concern that you have about your students who reside in grandparent-headed households?" The most common concerns were students' social, emotional, and academic needs and grandparent caregivers' wellbeing, involvement, and parenting style. Less frequent identified concerns were role modeling and awareness within schools. School personnel had very little prior knowledge or training about grandparents raising grandchildren. These findings can inform intergenerational learning between school personnel and grandparents raising grandchildren.